Możliwości symulacji procesów przemysłowych na elektronicznych maszynach cyfrowych - Abt, Stefan (Wydział Prawa i Administracji UAM, 1969)
The aim of the article is to attract the attention of the economists to the neglected appliance of computers, that are exploited to simulation of the economic processes. Under the simulation we understand not only the investigations, whose aim is to reduce the scale of time but also representation of some elements of the object, phenomenon, system or surrounding that enables the examination of the object. It can take place in the case of solving different mathematical problems (as for instance calculation of integrals), where in spite of analytical methods one uses Monte Carlo method and also in the examination of different economic processes. Different computers can be used as compositions that simulate the fate event or substitute the execution of the experiment. In the economical sciences it is a thing of great importance. The possibilities of simulation of the economical processes are presented in many examples from the problems of mass services, where for instance one describes the length of a queue or the optimal amount of staff across the simulation of behaviour of fictitious productive problems across the organizational systems, finishing with models that contain the factor of time. On the background of possibilities there are shown the perspectives of simulation of the economical processes.
Possibilities of Simulation of the Industrial Processes on Computers